Efektivitas Model Project-Based Learning dalam Meningkatkan Motivasi Belajar Siswa Kelas V pada Pembelajaran Sains - Nanlohy, Monalisa; Johannes, Nathalia Yohana; Ritiauw, Leonid; Maipauw, Musa Marsel (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study aims to examine the effect of the Project-Based Learning (PjBL) model on student learning motivation in science education for fifth-grade students at SD Negeri 66 Ambon. The research used a quantitative approach with a One-Group Pretest-Posttest Design. The study involved 30 students as the sample, selected using purposive sampling. Data collection was conducted using three techniques: observation, questionnaires, and documentation. The questionnaire instrument used consisted of 14 items with a Likert scale to measure various aspects of student learning motivation. The data obtained were analyzed using SPSS with descriptive analysis, Paired Sample T-Test, and N-Gain tests. The results show that after the implementation of the PjBL model, there was a significant increase in student learning motivation. The average motivation before the implementation of the PjBL model was 52.37% (moderate category), while after the implementation, the average increased to 63.97% (high category). The Paired Sample T-Test results showed a sig (2-tailed) value of 0.000, indicating a significant difference in student motivation before and after the intervention. Based on these findings, it can be concluded that the Project-Based Learning model is effective in enhancing student learning motivation, particularly in science education.